Dynamic modeling of particle size and porosity distribution in fluidized bed spray agglomeration - Otto, Eric; Dürr, Robert; Kienle, Achim; Bück, Andreas; Tsotsas, Evangelos (34th European Symposium on Computer Aided Process Engineering / 15th International Symposium on Process Systems Engineering, 2024)
Population balance modeling is a powerful to tool for the simulation of particle formation processes such as fluidized bed spray agglomeration (FBSA), where agglomerates are formed from primary particles by binary aggregation. In addition to the agglomerate volume, agglomerate porosity is important for the characterization of product particles since it affects various physical properties. In this contribution a new method is proposed to incorporate porosity into a population balance model. To this end an empirical relationship between the volume of solids within the agglomerate and its total volume including voids is utilized. Since this relationship is different for primary particles and agglomerates, respectively, the evolution of the number density distribution for both types of particles is modeled. The proposed population balance equations are validated by fitting three kinetic parameters to experimental data and comparing measured particle size distributions with model predictions, showing good agreement.
CRIS-Team Scopus Importer:2024-07-05
Keywords: agglomerate porosity; population balance modeling